Pengujian Efektivitas Tipe Pemangkasan Terhadap Produksi Tiga Varietas Semangka Pada Hidroponik Sistem Fertigasi (Drip Irrigation) - Rommy Andhika Laksono (Paspalum: Jurnal Ilmiah Pertanian, 2018)
Watermelon is an annual horticultural commodity that is easily damaged (perishable) so it must be consumed in a fresh state and must be marketed after harvest. Opportunities to increase production and productivity of watermelon in Indonesia are still very wide open both through the intensification and improvement of agricultural technology. The purpose of this study is to study and obtain the type of pruning that provides the highest production in hydroponics watermelon cultivation Fertigation system. The experiment was conducted at Screen House Mekarsari Fruit Garden Bogor Regency. from April to Augustus 2018. The research method used is experimental method and experimental design used is Single Factor Random Design, which consists of 9 treatments in 3 repetitions. The usual is a combination of two types of cutting (Toping and Pruning) and three watermelon varieties (Amara F1, Angela F1, and Batu Sengkaling). The data of the research using the analysis of variance based on F test of 5% level. If there is a real difference, the analysis is continued with DMRT (Duncan Multiple Range Test) test of 5% level.The results showed that the application of the cutting type had a significant effect on the stem diameter of 21 HST, 28 HST, and 35 HST, flowering age, harvest age, fruit diameter, and fruit weight per plant, three watermelon varieties in the hydroponic fertigation system. Application of Toping Trimming on Amara F1 Varieties provides the highest watermelon yields of 39, 24 tonnes per hectare or 8.24 kg per plant in the hydroponic fertigasi system.